PENGEMBANGAN MODEL PEMBELAJARAN TPS-RI UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI - Karima, Retmaniar; Rochimah, Ijah (LPMP Provinsi DKI Jakarta, 2025)
The results of observations and documentation are known that student skills in writing description text are still low so it is necessary to develop an innovative learning models that are contextual, meaningful and student-centered. This research aims to develop the Think Pair Share (TPS) learning model into Think Pair Share - Reflection and Improvement (TPS-RI) to improve the descriptive text writing skills of elementary school students. The type of research used is Research and Development (R&D) with the ADDIE model is Analyze, Design, Development, Implementation, and Evaluations. Data collection techniques use questionnaires, observation, essay tests, and documentation. The results of this research indicate that the product quality criteria is valid, practical, and effective. The assessment from expert validators obtained an average score of 3.59 in the very valid category. The results of the observation of learning implementation obtained an average score of 3.62 in the very good category, teacher responses obtained an average score of 3.47 in the very practical category, while student responses obtained an average score of 3.40 in the very practical category. The Implementation of TPS-RI learning model can improve the writing description text skill from the average score 54,40 to 83,60 with classical completeness is 96%. The results of this research indicate that development of TPS-RI learning model can improve student’s descriptive text writing skills.